(untitled) (Impetus, 2025)
Introduction. The lifestyle is built from activities or attitudes that influence the life of the human being; The university stage brings with it changes in behavior, so the challenge that is presented is to evaluate lifestyles at this determining moment for students. Objetive. Carry out construct validity of the categories addressed in the lifestyle questionnaire for university students proposed by Bazán and Carcausto in 2019 for Peru, to apply it to university students in Colombia. Methodology. Scoping review and the Population, Concept and Context (PCC) strategy was followed. The population are articles that are framed in the university population, the concept of each category is given by the four different dimensions of healthy lifestyles, which are physical-mental, social, ethical-moral and academic-family, and the context are healthy styles. Results. 53 articles were included in the review, in which a relationship was found between them, for which the importance of being addressed jointly and not only individually to recognize the complexity of this time in the life of beings is identified. humans. Conclusions. An adequate construct validity is evidenced, so it is necessary to continue with the reliability phase of the lifestyle questionnaire in order to analyze each of the activities that have an impact on the maintenance of healthy lifestyles and also create a program that allows maintaining a healthy lifestyle. healthy lifestyle for college students.